Nanoparticles therapy: inspiration from the mechanism by which SARS-CoV-2 disrupts autophagy - WANG, Zhaojunli; WANG, Qi; JI, Jiancheng; QIAN, Yuanyuan (Minerva Biotechnology and Biomolecular Research, 2023)
The epidemic outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) stands at 624,564,771 cases confirmed globally, with 6,601,510 cases of deaths (as per the WHO report on 2022 November 14th). Researchers dedicated to the mechanisms of infection and transmission in vivo, have developed various antiviral drugs against SARS-CoV-2 infection. Such studies have indicated that SARS-CoV-2 could hijack autophagy machinery to trigger the accumulation of autophagosomes. In contrast, the hyperaccumulation of autophagosomes activates the apoptosis pathway in the infected cells and disrupts the replication of the virus. Approximately 50% of drugs that FDA approved for clinical therapeutics are modulators of autophagy. Hence, these drugs restrict the virus reproduction by inhibiting autophagy. However, there are potential side effects of these traditional autophagy modulators, which limit their utilization. In this review, we probe into the interaction between SARS-CoV-2 and autophagy, as well as the potent therapeutics for the SARS-CoV-2 hijacking autophagy pathway. Among these, nanoparticles targeting autophagy may become an effective strategy for rescuing the infection of SARS-CoV-2. This implies drug research and developments in the treatment of SARS-CoV-2.